1996
DOI: 10.1093/jnci/88.10.661
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Symptoms and Disease-Free and Overall Survival in Women With Stage II Breast Cancer

Abstract: In the context of far more potent medical factors, the contribution of psychological factors to disease-free and overall survival is likely to be relatively small. Future research should focus on specific theory-driven predictors rather than on general psychological symptoms. Moreover, it should be based on clinical studies using a controlled, prospective design, in which the effects of medical factors may be distinguished and psychological predictors are clear antecedents of survival outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
1
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(53 citation statements)
references
References 22 publications
2
49
1
1
Order By: Relevance
“…Our results were consistent with the negative finding of other studies [121,122], which investigated the potential relationship between psychiatric morbidity and survival in cancer and non-cancer patients.…”
Section: Geriatric Depression Scoresupporting
confidence: 93%
See 1 more Smart Citation
“…Our results were consistent with the negative finding of other studies [121,122], which investigated the potential relationship between psychiatric morbidity and survival in cancer and non-cancer patients.…”
Section: Geriatric Depression Scoresupporting
confidence: 93%
“…Tross S et al [121] prospectively examined the contribution of potential psychological predictors to length of disease-free and overall survival in 280 women with stage II breast cancer. However, the study failed to provide evidence that psychological factors (including depression) contributed to the length of disease-free or overall survival of these women.…”
Section: Geriatric Depression Scorementioning
confidence: 99%
“…The Chinese version of symptom checklist-90 (SCL-90) (Wang, 1984), a 90-item multidimensional self-report inventory aiming to evaluate a broad range of psychological problems and symptoms of psychopathology, was adopted as the major measurement for psychological status. The reliability, validity and utility of SCL-90 have been proved not only by psychiatric and psychological studies (Peveler et al, 1990;Schimitz et al, 1999;Prins et al, 2001), but also been demonstrated by studies in cancer patients (Derogatis et al, 1983;Tross et al, 1996;Lerman et al, 2011). The data from SCL-90 were calculated and compared with the normal range in Chinese reported by Jin et al (1986.…”
Section: Methodsmentioning
confidence: 99%
“…Several prospective and intervention studies have found an association between psychosocial factors and outcome (Stavraky et al, 1988;Spiegel et al, 1989;Greer et al, 1990;Fawzy et al, 1993;Molassiotis et al, 1997;Butow et al, 1999). Other studies have failed to find any association (Jamison et al, 1987;Tross et al, 1996).…”
mentioning
confidence: 99%